1989
DOI: 10.1007/bf00595895
|View full text |Cite
|
Sign up to set email alerts
|

Serial ultrasonic examination to differentiate biliary atresia from neonatal hepatitis ? special reference to changes in size of the gallbladder

Abstract: We performed serial ultrasonic examinations to differentiate biliary atresia from neonatal hepatitis. The subjects studied were 144 children (100 normal neonates and infants, 31 patients with neonatal hepatitis and 13 patients with biliary atresia). They were examined by ultrasound before, during and after feeding. In 97 out of 100 normal children and all patients with neonatal hepatitis, the gallbladder was identified, and the change in size following oral feeding was observed. In four children with severe ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 13 publications
1
19
0
Order By: Relevance
“…We therefore may postulate that the presence of the gallbladder is also important in diagnosis of hepatitis and its absence may further support the diagnosis of BA, as all the operated cases did not reveal gall bladders as was suggested on USS. Ikeda et al, [13] in four children with severe neonatal hepatitis which could not be differentiated from biliary atresia by clinical and laboratory data, readily identified the gallbladder and observed the change in the size following oral feeding, as was seen in this study. In 8 of 13 of their patients with biliary atresia, they identified a small gallbladder whose size was not affected by oral feeding, as confirmed in one of the patients in the present study.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…We therefore may postulate that the presence of the gallbladder is also important in diagnosis of hepatitis and its absence may further support the diagnosis of BA, as all the operated cases did not reveal gall bladders as was suggested on USS. Ikeda et al, [13] in four children with severe neonatal hepatitis which could not be differentiated from biliary atresia by clinical and laboratory data, readily identified the gallbladder and observed the change in the size following oral feeding, as was seen in this study. In 8 of 13 of their patients with biliary atresia, they identified a small gallbladder whose size was not affected by oral feeding, as confirmed in one of the patients in the present study.…”
Section: Discussionsupporting
confidence: 77%
“…When we compare the findings in the present study to that of Shi-Xing lee et al [2] who retrospectively analyzed the sonograms of 20 children with biliary atresia, TC in 10 cases was 30-60mm, 2 cases did not have a demonstrable gall bladder, all liver showed hepatomegaly and were heterogenous and they concluded that the degree of heterogenicity and hepatomegaly was proportional to liver fibrosis and able to indicate the duration and prognosis of the disease [2,13]. The mean TC width in the present study was 2.62 +1.23 mm with 9 of our study subjects having TC width between 3.5 -4.7mm.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Cirrhosis and secondary hepatic cellular carcinoma, as well as portal hypertension that is sonographically diagnosed by additional DDS, only occur secondary to hepatitis, coagulopathies, umbilical catheters and systemic disease, or due to chronic inherited disease such as cystic fibrosis, autosomal-recessive polycystic disease and biliary atresia [109]; the latter still poses a diagnostic challenge, as clinical findings and scintigraphy may be nonspecific. Congenital hepatitis and hypoplasia/atresia of the bile ducts may cause a similar appearance of liver parenchyma in the neonate, but there are some clues that US can offer to help in establishing the diagnosis: the small size of the gall bladder (< 2 cm maximum length) and the ªtriangle signº at the porta hepatis (residual fibrotic, echogenic material from the hepato-choledochal duct) may hint at biliary atresia [110,111]. Early diagnosis is essential for successful treatment by Kasais' operation and may help in preventing or postponing the need for liver transplantation.…”
Section: Liver Spleen and Pancreasmentioning
confidence: 96%
“…To make a definitive diagnosis in a patient with prolonged jaundice, a series of routine diagnostic investigations including ultrasonography, hepatobiliary scintigraphy, endoscopic retrograde cholangiopancreatography [4][5][6][7] are usually performed. Despite these investigations, the exact diagnosis may still not be forthcoming and surgical intervention is traditionally the next step.…”
Section: Introductionmentioning
confidence: 99%